Edukasi Literasi Digital Penggunaan E-Commerce Bagi UMKM Di Pasar Sentral Kota Medan - Rahayu, Sri Endang; Polem, Naufal Maulana; Kinanti, Fani Rasya; Yanti, Voni; Prabowo, Agung (Maslahah: Jurnal Pengabdian Masyarakat, 2024)
Some MSMEs may face challenges in adopting and utilizing E-commerce platforms due to a lack of understanding of digital literacy. Digital literacy education is key to helping MSMEs overcome barriers to engaging effectively in e-commerce. Medan City Central Market is a vital economic and trade center in the Medan city area. MSMEs in the Central market sell various kinds of products. However, with the existence of e-commerce, product sales have decreased. The decline in consumers visiting and buying at this central market. The objectives of this service are: 1). Assess and analyze the extent to which MSMEs in the Medan City Central Market have digital literacy in the use of E-commerce, 2). Identifying the obstacles and challenges faced by MSMEs in the Medan City Central Market in adopting and utilizing E-commerce, 3). Identifying the benefits that MSMEs can obtain in the Medan City Central Market through increasing digital literacy in the use of E-commerce. The results obtained are that there are still many MSME players who do not understand or do not use e-commerce platforms to sell. However, there are also several traders who have used e-commerce. From the results of digital literacy that has been carried out, it is successful in helping one of the traders who has a shop, namely the Jenna Batik shop which sells women's clothing, by helping create a Shopee account and also financial reports from the shop. After we also compared online and offline sales and it was found that selling offline or selling in stores directly in the central market still provided greater profits.